HUBUNGAN ANTARA POLA ASUH DAN REGULASI EMOSI PADA REMAJA AKHIR USIA 19-21 TAHUN - Ruth Wijaya, Jemima; Kartasasmita, Sandy (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Late adolescence is marked by dynamic physical, cognitive, and emotional changes. Emotional regulation is an essential skill influenced by parenting styles. This study aims to analyze the relationship between parenting styles and emotional regulation abilities in late adolescents (aged 19–21 years) in DKI Jakarta. The study used a quantitative correlational design involving 510 adolescents living with their parents. The instruments used were the Parenting Styles and Dimensions Questionnaire (PSDQ) and the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA). Pearson correlation analysis showed a significant positive relationship between authoritative parenting (r = 0.142; p = 0.035) and authoritarian parenting (r = 0.217; p = 0.009) with emotional regulation. In contrast, permissive parenting showed no significant relationship (r = 0.021; p = 0.801). These findings emphasize the importance of balanced, consistent, and warm parenting practices in supporting the development of adaptive emotional regulation in late adolescents. ABSTRAK Masa remaja akhir ditandai oleh perubahan fisik, kognitif, dan emosional yang dinamis. Regulasi emosi merupakan keterampilan penting yang dipengaruhi oleh pola asuh orang tua. Penelitian ini bertujuan untuk menganalisis hubungan antara pola asuh orang tua dan kemampuan regulasi emosi pada remaja akhir (usia 19–21 tahun) di DKI Jakarta. Penelitian ini menggunakan desain korelasional kuantitatif dengan melibatkan 510 remaja yang tinggal bersama orang tua. Instrumen yang digunakan adalah Parenting Styles and Dimensions Questionnaire (PSDQ) dan Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA). Analisis korelasi Pearson menunjukkan hubungan positif yang signifikan antara pola asuh otoritatif (r = 0,142; p = 0,035) dan otoriter (r = 0,217; p = 0,009) dengan regulasi emosi. Sebaliknya, pola asuh permisif tidak menunjukkan hubungan yang signifikan (r = 0,021; p = 0,801). Temuan ini menegaskan pentingnya pola pengasuhan yang seimbang, konsisten, dan penuh kehangatan dalam mendukung pengembangan regulasi emosi yang adaptif pada remaja akhir.